Factors influence consumer trust in shopping product online / Maslina Mahazir - Mahazir, Maslina (Faculty of Business and Management, 2019)
This title of this research is “Factors Influence Consumer Trust in Shopping Product Online”. The main objective of this research is to examine the relationship between factors influence consumer’s trust towards shopping product online. The consumer’s trust consist of reputation, business size, perceived service quality, website, information security and reference group which have been identified in order to investigate whether or not these factors have influence towards trust in shopping product online. The independent variables in this research are factors of consumer’s trust while the dependent variable is trust. Hence, the questionnaires were distributed and 100 respondents were obtained with convenience sampling will used as sampling technique that was analyzed with Statistical Program for the Social Sciences (SPSS) version 22. The results have shown that website, information security and reference group have a positive significant relationship towards trust. Thus, there are three variables are not significant relationship which is reputation, business size and perceived service quality towards trust. While, the level of consumer’s trust is moderate.